Nanotechnology for molecular imaging of atherosclerosis: current design and approaches - Maslizan, Mardhiah; Mat Azmi, Intan Diana; Mohamad Jaafar, Adila; Haris, Muhammad Salahuddin (Akademia Baru Publishing, 2021)
Atherosclerosis complications such as myocardial infarction or stroke is still one of the most critical causes of death worldwide. Advance and innovative diagnostic technologies are urgently required to discover an early stage of the disease, such as plaque instability and thrombosis. A combination of molecular imaging probes based on well-designed nanomaterials with leading-edge imaging methods is currently concreting the direction for novel and distinctive approaches to examine the inflammatory growth in atherosclerosis. Over the past several decades, an exceptional understanding of the biological nature of atherosclerosis provides unique opportunities to better treat atherosclerotic disease with targeted imaging and nanomedicines. Consequently, tremendous development has been initiated in the nanotechnology application; the leading engineering tools working at molecular range, which is designed for diagnostic and therapeutic approach, called theranostic. This review underlying ideas involving the potential and development of molecular imaging technologies that had been invented for studying atherosclerosis. We envisage that many molecular imaging methods will become valuable assistants to the clinical management of targeted treatment in the atherosclerosis disease together with their challenges and future perspective in clinical translation.